Pendampingan Pembuatan Konten Virtual Tourism sebagai Inisiasi Living Lab Cagar Budaya Kampoeng Heritage Kayoetangan - Aniesa Samira Bafadhal (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The management of tourist destinations that not only have a function as a cultural heritage site but also residents' homes such as Kampoeng Wisata Heritage Kojoetangan, Malang City has a tendency to contain several problems that must be faced together because it is feared that if it is not immediately fixed it will only be a short-lived cultural euphoria. One solution that can be used is through the initiation of a living labbased collaboration in the form of co-creation of virtual tourism content creation based on virtual reality websites by considering the information and needs of stakeholders, namely, local government, destination managers, tourists, residents in Kampoeng Wisata Heritage Kojoetangan. .This community service is an implementation of action research in the form of assistance to destination managers, namely the Tourism Awareness Group